3a-9=7+3a-a

Simple and best practice solution for 3a-9=7+3a-a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-9=7+3a-a equation:


Simplifying
3a + -9 = 7 + 3a + -1a

Reorder the terms:
-9 + 3a = 7 + 3a + -1a

Combine like terms: 3a + -1a = 2a
-9 + 3a = 7 + 2a

Solving
-9 + 3a = 7 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-9 + 3a + -2a = 7 + 2a + -2a

Combine like terms: 3a + -2a = 1a
-9 + 1a = 7 + 2a + -2a

Combine like terms: 2a + -2a = 0
-9 + 1a = 7 + 0
-9 + 1a = 7

Add '9' to each side of the equation.
-9 + 9 + 1a = 7 + 9

Combine like terms: -9 + 9 = 0
0 + 1a = 7 + 9
1a = 7 + 9

Combine like terms: 7 + 9 = 16
1a = 16

Divide each side by '1'.
a = 16

Simplifying
a = 16

See similar equations:

| 6x-3(x+9)=5x-17 | | (3x^2)+18x-16=2-7x | | 3(x-11)=14*34(16+x)-78 | | -6(3m-10)=6-9m | | 30y^2-25y+5=0 | | y^2-121=0 | | y+5=10 | | -[8z-(15z+8)]=8+(6z+2) | | -17p-5(2-5p)=4(p-4)-38 | | X^2+25x+600=0 | | -24=v+2 | | x^2+4x+2=y | | x-14=22 | | 2.7-2y=3 | | -19=14+x | | 25+x=50 | | 64k^2=16 | | 2.5-2y=4 | | -12=p+9 | | 4+a=2 | | -14=v+2 | | 20+k=27 | | x+2*2=6 | | -15+m=-22 | | k-10=-22 | | 2-2y=4 | | 26x^2-27x=0 | | -2p^2= | | 25x^3+10x^2-15x= | | k-10=-23 | | 5=3x-y | | -6=a-10 |

Equations solver categories